علاقة إدارة الوقت بمستوى ضغوط العمل من وجهة نظر عمّال المركبات الرياضية دراسة ميدانية لمركبات ولايتي سطيف والمسيلة - قاسمي, فيصل; بلخير, عبد القادر (Université de M'sila, 2011)
تناولنا في هذا البحث العلاقة بين إدارة الوقت ومستوى ضغوط العمل لعمال المركبات الرياضية، بخلاف الدراسات السابقة التي درست هذه العلاقة في مجالات علم النفس الصناعي وعلوم التسيير والإدارة والعلوم الاقتصادية، هدفت هذه الدراسة إلى التعرف على الفروق بين عمّال المركبات الرياضية في أدائهم للأعمال والمهام الإدارية والفنية والشخصية وكذلك الفروق في تعرضهم لآثار الضغوط المهنية وفقا لمتغيرات:"الجنس، الحالة الاجتماعية، المؤهل العلمي، الخبرة المهنية "، كما قامت الدراسة بتقديم رؤية مقترحة تسهم في تحسين إدارة الوقت وكذلك تحديد طرق التغلب على الإحساس بالضغط لدى عمال المركبات الرياضية . وتكوّن مجتمع الدراسة من جميع الموظفين في المنشآت الرياضية في كل من ولايتي "سطيف والمسيلة"، البالغ عددهم (158) موظفا وموظفة، وطبقت الدراسة على عينة عشوائية بسيطة مكونة من (89) موظفا وموظفة، أي حوالي (56%) من مجتمع الدراسة الأصلي خلال العام الدراسي"2010/2011"، وقد استخدم الباحث المنهج الوصفي التحليلي مع استخدام أداة الدراسة الرئيسية وهي الاستبيان، الذي اشتمل على (106) عبارة مقسمة على خمسة (05) محاور. ومن أهم النتائج المتوصل إليها في هذه الدراسة : - وجود فروق ذات دلالة إحصائية للأعمال والمهام التي يقوم بها العامل وقت الدوام تعزى باختلاف الجنس والحالة الاجتماعية والمؤهل العلمي ،ولا توجد هذه الفروق في حالة اختلاف سنوات الخدمة. - وجود فروق ذات دلالة إحصائية لإجابات أفراد العينة حول آثار ضغوط العمل التي يتعرض لها العمّال تعزى باختلاف الجنس والخبرة، ولا توجد هذه الفروق في حالة اختلاف الحالة الاجتماعية والمؤهل العلمي . - إدارة الوقت بكفاءة دور في التقليل من آثار ضغوط العمل . - توجد علاقة طردية بين هدر الوقت وزيادة آثار ضغوط العمل . - تقديم العمّال رؤية مقترحة تسهم في تحسين إدارة الوقت من خلال الحرص على الحضور للمنشأة قبل الموعد المحدد وعدم مغادرتها قبل نهاية الدوام والحرص على توظيف استخدام أنظمة المعلومات الحديثة في العمل. - وبينت الدراسة أن العاملين في المنشآت الرياضية المبحوثة تظهر عليهم آثار جسمية سلبية نتيجة الإحساس بالضغط، تتمثل بالشعور بالتعب والإنهاك، كما بينت الدراسة أن العاملين يستخدمون العديد من الطرق بشكل فعال للتغلب على الإحساس بالضغط مثل الحرص على حل المشاكل العائلية التي قد تؤثر على العمل، الحرص على إدارة الوقت بشكل جيد، الحرص على التواصل مع الآخرين . هذه النتائج التي توصلنا إليها تحتم على إدارة المنشآت الرياضية الاهتمام بالوقت وإدارته بكفاءة ليصبح جزءا من الثقافة الإدارية التنظيمية. وزيادة الوعي عند العاملين فيما يتعلق بموضوع الضغوط المهنية وتدريبهم على الطرق الملائمة لمواجهتها. OUTLINE In this study we are dealing with the relationship between time management and the level of work stress for sport complexes’ workers. Unlike previous studies that examined this relationship in the areas of industrial psychology , science of management, administration and economic science, this study aimed to identify the differences between sport complexes’ workers in their performance of the administrative, technical and personal tasks, as well as differences in their exposure to the professional pressure’s effects, according to the variables: (gender, marital status, educational qualification and professional experience) The study also proposes a new vision that may contribute to better time management, as well as identifies ways to overcome the pressing sense of the sport complexes’ workers. The study population consisted of all staff in the sports complexes in each of the states (Setif and M’sila), totaling 158 male and female employees, and implemented a study on a simple random sample of 89 male and female employees, means about (56%) of the original population of the study during the academic year 2010 / 2011.The researcher used the descriptive analytical method using the main tool of study which is the questionnaire, including (106) phrase divided on 05 topics. The most important findings in this study: The presence of statistically significant differences for the work and functions performed by the worker at the working time attributed to gender, marital status, educational qualification, and these differences are absent in the case of differentiations in the years of service. The presence of statistically significant differences for the answers of respondents about the effects of work stress experienced by workers due to differentiation in gender, experience, and there is no there is no such differences in the case of social status differentiation and educational qualification. There is a great important role to the efficient time management in minimizing the effects of job stress. There is a direct correlation between the waste of time and the increase the work stress effects. Provide workers with a proposed vision contributes in better time management by ensuring the early presence to the facility and never leave it before the end of working hours and keep in mind the use of modern information systems during the work. The study shows that sports facilities workers under examination , have signs of physical negative resulted from their feeling of pressure; eg : feeling tired and exhausted .It also shows that workers use several methods to effectively overcome the sense of pressure, such as solving family problems that may affect the work, care to manage their time very well and communicate with others. These results we have necessitate on the sports facilities administrations to pay attention to run efficiently their time to become part of organizational management culture, increasing awareness among workers on the subject of professional pressures and training them the appropriate ways to face them.
Keywords: إدارة الوقت - ضغوط العمل - المركبات الرياضية